Company Responsibility for Environmental Damage Caused by Mineral and Coal Mining - Haddat, Chairil; Budiarsih (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Mining activities in Indonesia provide a large economic contribution, but on the other hand have the potential to cause significant environmental damage. Environmental damage due to mining activities is a serious problem that continues to be in the public and academic spotlight. To ensure legal protection for the environment and affected communities, the Indonesian legal system regulates various forms of legal liability, including civil liability. This study aims to determine several important targets related to regulatory changes in the mining sector in Indonesia, especially regarding the involvement of Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining. This research method uses normative legal research, with a statutory approach and a conceptual approach. The sources of legal materials used are primary, secondary, and tertiary legal materials, and the analysis of the materials carried out is qualitative analysis. The collection of legal materials was carried out through the literature study method. The results of the discussion show that there are still many administrative violations that have an impact on environmental sustainability, due to weak supervision and lack of transparency. Mining companies have strong legal responsibilities based on laws and regulations. However, in its implementation, many violations and lack of supervision are still found. Therefore, it is necessary to strengthen regulations and reform the environmental administration system as a whole.